Optimising Teaching Proficiency in the Digital Age: Integration of Effective E-Learning Tools in Schooling - Onesme Niyibizi (Journal of Learning for Development, 2025)
This study explored how integrating e-learning tools, specifically free ‘Google Workspace for Education’ tools, enhances teaching proficiency and student engagement in the digital age within Rwandan secondary schools. By employing a phenomenological approach, interviews were conducted with 166 secondary teachers from four purposefully selected secondary schools in Rwanda. The research found that while nearly 95% of teachers were aware of Google tools and 98% regularly used Google Classroom, a significant number (40%) underutilised other features like Google Forms and Sheets. Over 90% of the teachers surveyed reported benefits, such as improved collaboration and student engagement, but over 75% also cited barriers including limited access to digital facilities and insufficient training, with 60% expressing concerns about internet and device access. Pedagogical approaches varied, with roughly 50% of the teachers shifting towards student-centered methods. Strong qualitative evidence from over 85% of the teachers indicated increased student engagement and participation. The findings highlight the critical need for comprehensive professional development and improved infrastructure to maximise the effectiveness and sustainability of e-learning tool integration in education.